2020
DOI: 10.3928/00989134-20191118-02
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Technology to Older Adults: Modalities Used by Student Mentors and Reasons for Continued Program Participation

Abstract: The current study examined teaching modalities used by college students participating in an intergenerational, service-learning program that helps older adults learn technology and described reasons for older adults' continued participation in this program. Qualitative data analysis was completed using student-maintained observation logs from approximately 200 older participants. Several different teaching modalities used by student mentors were identified, including observing and listening, writing down infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…However, few studies reveal the relationships between gratitude, care willingness and attitude toward the elderly (Zhang, et al , 2016). Moreover, LoBuono et al (2020) reported that “more information is needed to understand best practices for teaching older adults how to use technology and understand older adults’ reasons for continued participation in an intergenerational program” (p. 15). To promote better social connectedness, reduce loneliness and social isolation, interventions are needed (O'Rourke et al , 2018).…”
Section: Intergenerational Service-learningmentioning
confidence: 99%
“…However, few studies reveal the relationships between gratitude, care willingness and attitude toward the elderly (Zhang, et al , 2016). Moreover, LoBuono et al (2020) reported that “more information is needed to understand best practices for teaching older adults how to use technology and understand older adults’ reasons for continued participation in an intergenerational program” (p. 15). To promote better social connectedness, reduce loneliness and social isolation, interventions are needed (O'Rourke et al , 2018).…”
Section: Intergenerational Service-learningmentioning
confidence: 99%
“…Researchers have investigated various modes of learning to determine older adults’ preferences when learning to use mobile devices. For instance, Pang et al [ 21 ] conducted a design prove study of an interactive help kiosk, Chiu et al [ 38 ] conducted a focus group of a small-group tutoring approach, LoBuono et al [ 39 ] observed the utility of intergenerational learning by college students, and den Haan et al [ 40 ] ran a field study of peer-to-peer community learning. Although findings from these studies were mixed as to which learning methods older adults preferred or found effective, they share a common preference: a collaborative approach implemented by peer support, interpersonal communication, and community-based programs.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the heterogeneous character of the older age group, especially within a digital context (Quan-Haase et al, 2018), studies recommend the combination of several teaching approaches enabling the elderly's adoption and use of technologies, such as observational learning, collaborative learning, providing step-by-step explanations and allowing learning by trial and error (LoBuono et al, 2020). This study confirms such recommendations, since it has evidenced a necessary alignment between techniques and methods to be adopted by the instructors with the older students' specific demands.…”
Section: Didactics and Methodological Strategiesmentioning
confidence: 99%
“…Another theme evidenced in the results was the preservation of the students' autonomy during the learning process, in which two conditions were identified: not to do it for the older learners and to allow them to interact by themselves with the technologies, without the instructors' interference in the practical activities. The participants' comments regarding their preferences and learning objectives should be recognised in the digital literacy programmes (Tyler et al, 2020;LoBuono et al, 2020). In this sense, the goal is to promote the students' development of self-responsibility in the learning process and their appreciation of knowledge empowerment (Boulton-Lewis;Tam, 2018) In the light of all recommendations offered by the older students to instructors of digital literacy programmes, it is possible to prove the complexity of the theme of teaching, and of the adoption and use of technology by the older users, inasmuch as various aspects are involved in these processes (Doll;Machado;Cachioni, 2016).…”
Section: Didactics and Methodological Strategiesmentioning
confidence: 99%
See 1 more Smart Citation